Metode Tracking 3D Image dalam Teknologi Augmanted Reality untuk Pembelajaran Animasi Sekolah Lanjutan Tingkat Atas - Hadrila P A; Y Yuhandri; S Sumijan (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Augmented reality is a technique that combines two-dimensional and three-dimensional virtual objects into a real three-dimensional scope and then projects these virtual objects in real time. The use of markers in this application is chosen apart from being suitable for implementation as learning and also tends to be fast in terms of reading on the process of the emergence of 3-dimensional objects in visual Form. This research aims to be a learning medium for the 12 Principles of Animation at the high school level. The method used in this research uses the 3D Image tracking method, which has four stages, namely 3 Dimensional Model Development, Marker development, Model implementation into development tools, Augmanted Reality Application Implementation, Dataset consists of 12, 3 Dimensional images representing each of the 12 Principles of Animation. This research produces animated Augmanted Reality digital learning media that can attract student interest and make students understand more quickly. Reference: The use of animated Augmanted Reality learning media makes learning active, creative, effective and fun.